Antimicrobial Susceptibility of Microbiota in Bacterial Vaginosis Using Fluorescence In Situ Hybridization - Alexander Swidsinski; Alexander Guschin; Lorenzo Corsini; Vera Loening-Baucke; Lenka Podpera Tisakova; Sonja Swidsinski; Jack D. Sobel; Yvonne Dörffel (Pathogens, 2022)
Background: Testing of antibiotic resistance of intact vaginal microbiota in pure culture is not feasible. METHODS: Metronidazole, antiseptic octenisept®, antimycotic ciclopirox, bacterial probiotic Lactobacillus crispatus, yeast probiotic Saccharomyces boulardii, Gardnerella-phage-endolysin named phagolysin and phagolysin in combination with probiotics were tested for bacteriolytic activity. Included were vaginal swabs from 38 random women with Amsel-confirmed bacterial vaginosis (BV). Test aliquots were incubated by 37° for 2 and 24 h. Gardnerella, low G+C, Atopobium, lactobacilli, Lactobacillus iners and crispatus, Prevotella-Bacteroides, and Gammaproteobacteria microbial groups were quantified using fluorescence in situ hybridization (FISH). Results: The probiotic strain Lactobacillus crispatus demonstrated the weakest bacteriolytical effects, followed by metronidazole. Both had no impact on Gardnerella species, instead lysing Prevotella-Bacteroides, Enterobacteriaceae (by L.crispatus) or LGC, Atopobium and Prevotella-Bacteroides (by metronidazole) groups of the microbiota. Cytolytic activity on Gardnerella was highly pronounced and increased from octenisept to ciclopirox, phagolysin, phagolysin with L.crispatus, being best in the combination of phagolysin with S.boulardii. Universally active ciclopirox and octenisept® suppressed nearly all microbial groups including those which are regarded as beneficial. Phagolysin had no effect on naturally occurring Lactobacillus crispatus. Conclusions: FISH susceptibility testing allows unique efficacy evaluation of individually adjusted topical therapy without microbial isolation facilitating optimal therapy choice.